PENGEMBANGAN SLB-A YAPTI MAKASSAR SEBAGAI SEKOLAH BLIND CENTER MELALUI PEMBELAJARAN BERBASIS KOMEDI (KOMPUTER, INTERNET, DAN AUDIO) - Marhani, Marhani (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2017)
the right strategy in solving learning problems at YAPTI Makassar SLB-A is through COMEDI-based learning (Computer, Internet, and Audio). The results showed that YAPTI Makassar's SLB-A development as a Blind Center school through KOMEDI (Computer, Internet, and Audio) learning was very appropriate, because: blind students were easier to understand something through auditory learning, in accordance with the teaching principles for blind children, interesting , and foster the spirit of student learning, and can make certain material developments. YAPTI Makassar SLB-A development as a Blind Center school through KOMEDI learning (Computers, Internet, and Audio) can create a conducive learning environment, learning innovations are increasingly developed, the order of learning implementation is well achieved, and school performance has increased.